A receptor guanylyl cyclase expressed specifically in olfactory sensory neurons. - Fülle, H J (1995)
We have cloned an additional member (GC-D) of the membrane receptor guanylyl cyclase [GTP pyrophosphate-lyase (cyclizing), EC 4.6.1.2] family that is specifically expressed in a subpopulation of olfactory sensory neurons. The extracellular, putative ligand-binding domain of the olfactory cyclase is similar in primary structure to two guanylyl cyclases expressed in the retina but diverges considerably from other known guanylyl cyclases. The expression of GC-D RNA is restricted to a small, randomly dispersed population of neurons that is within a single topographic zone in the olfactory neuroepithelium and resembles the pattern of the more diverse seven-transmembrane-domain odorant receptors. These observations suggest that GC-D may function directly in odor recognition or in modulating the sensitivity of a subpopulation of sensory neurons to specific odors.